Prevalence of Blood Group Trait among Scheduled Castes of Patna (Bihar): Exploring the Prevalence of Blood Group Trait among Scheduled Castes in Patna (Bihar), India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In context to India, the Meddelian trait is is known to have caste-variation. That means caste is the factor for evolution of the forces of micro-evolution leading to macro-evolution which ultimately influence the biological structure of human populations. India is inhabited by people of great diversity, different creeds and customs forming what may be designated as multiple (or plural) society. There are about 3000 castes in India, some have genesis in castel stock while others are occupational, linguistic, religious and territorial entities. Each caste is a social unit or what may be called ‘monopolistic guild’ in itself. All these groups are not entirely independent usually people belong to two or more of such groups at the same time. The climate of India has many regional variations determined by locations, altitude, distance from the sea or the mountains and the general relief. India is divided into eight climatic regions based on the monthly value of temperature and precipitation. India is a Union comprising 25 States and 7 Union Territories and these may be categorized into six zones (North, West, East, Central, South India and Islands).In intension of understanding caste factor in prevalence of Mendelain trait, the present study is restricted to its study in terms of blood group(s) among the four prominent Scheduled Caste of Patna, Bihar, India. Namely, the Dusadhs, the Chamars, the Pasis and the Musahars.